HUBUNGAN PENGETAHUAN IBU DAN PELAKSANAAN PROGRAM IVA DENGAN PEMERIKSAAN IVA PADA IBU PASANGAN USIA SUBUR DI PUSKESMAS WARA KOTA PALOPO - Ny. Hikma (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
Background: Visual Inspection with Acetic Acid (IVA) is a simple way to detect cervical cancer as early as possible. IVA is the examination of the cervix (cervical) by looking directly (with the naked eye) cervix after cervical neck with a solution of acetic acid 3-5%.Objective: To know the factors associated with the IVA examination in the Mother Age Fertile Age at Wara Palopo Public Health Center of 2017.Method: This research use analytic survey with cross sectional study approach. The population in this study were all mothers of fertile age couples in Wara Puskesmas of East Luwu Regency as many as 6,276 people. The sample in this research is part of population with sampling technique yiatu purposive sampling counted 98 people. Data collection through primary data (questionnaire) and secondary data. The data were processed using Statistical Product and Servise Solutions (SPSS) version 20.0 and analyzed univariat and bivariate with chi square statistical test and presented in the form of frequency distribution table.Results: There is a knowledge relationship with IVA examination (p Value = 0.002 <0.05 and there is an implementation relationship with IVA examination (p Value = 0,000 <0.05).Conclusion: There is a relationship of knowledge with IVA examination at Puskesmas Wara Kota Palopo Year 2017. There is an implementation relationship with IVA examination at Wara Palopo Public Health Center of 2017 Keywords : IVA Examination, Knowledge, Implementation